Skala Regulasi Emosi: Analisis Reliabilitas dan Validitas Konstruk melalui Pendekatan Confirmatory Factor Analysis (CFA) - Putri, Rani Mega; Wisma, Nur; Rozzaqyah, Fadhlina; Ar, Silvia; Ikbal, Muhammad; Muti’ah, Aulia (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
Emotion is a response shown by an individual to an event or stimulus that can affect his mental state. These emotions require control within the individual to be able to produce positive behavior, feelings and mental states in the process of emotional regulation. Measuring emotional regulation is needed to be able to describe a person's emotional control state. The aim of this research is to produce a valid and reliable emotional regulation scale. This research method is a research and development method with the ADDIE model. The population in this study was 2996 Class XI high school students in Ilir Barat 1 District, Palembang City. The total sample for this research was 102 respondents taken randomly. This research data processing uses SPSS with the product moment formula and factor analysis with a confirmatory factor analysis approach. The results of the research show that the content validity of experts states that 95% of the scale is suitable for use, and the emotional regulation scale prepared is constructively valid with 45 items with a Cronbach's alpha reliability value of 0.948. It was concluded that the emotional regulation scale was suitable for use with a larger and more diverse group of respondents.